2018
DOI: 10.1680/jadcr.17.00165
|View full text |Cite
|
Sign up to set email alerts
|

Study of using light-burned dolomite ores as raw material to produce magnesium oxysulfate cement

Abstract: Magnesium oxysulfate cement (MOS) prepared by light-burned dolomite has excellent performance in terms of light weight, high strength and low carbon dioxide emission. In this research, dolomite ores are used to produce MOS cement at different calcination temperatures and calcination times; the parameters investigated are the rate of loss on ignition, free lime (f-CaO), dihydrate gypsum (CaSO 4 Â2H 2 O) and impact of active magnesium oxide (α-MgO) content exerted on the setting time and compressive strength of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…When bischofite was dissolved in water, MgCl 2 -H 2 O of a certain concentration was formed. The ratio of m f added to the bischofite was a function of the Ba: f (m f /m Bi ) = f (Ba), which can be calculated according to Equation (17). As shown in Table 3, the actual measured function is expressed as f (m f /m Bi ) = f (Ba).…”
Section: Relationship Between the Amount Of Water In Brine And Bischomentioning
confidence: 99%
See 1 more Smart Citation
“…When bischofite was dissolved in water, MgCl 2 -H 2 O of a certain concentration was formed. The ratio of m f added to the bischofite was a function of the Ba: f (m f /m Bi ) = f (Ba), which can be calculated according to Equation (17). As shown in Table 3, the actual measured function is expressed as f (m f /m Bi ) = f (Ba).…”
Section: Relationship Between the Amount Of Water In Brine And Bischomentioning
confidence: 99%
“…The MgO content in dolomite is one-third of that of magnesite; therefore, the mechanical performance of MOC prepared with dolomite raw material is poor [14], especially magnesium oxychloride cement foam concrete (MOCFC) made from porous material [15]. Dolomite has already been tested as a raw material for producing MgO-based cements such as magnesium oxychloride cement [16], magnesium oxysulfate cement [17] and magnesium phosphate cement [13]. However, few studies have been conducted using CDP and LMP as the raw materials to produce MOC material, and only a few scholars have probed the performance of MOC made from mixed materials [18].…”
Section: Introductionmentioning
confidence: 99%
“…Half-calcined dolomites (HCDs) are of industrial importance as a source of MgO for construction, 1,2 catalysis, 3,4 and biomaterials; 5 as an absorbent for pollutant gases (H 2 S, SO x , and CO 2 ); 6–10 and as a scrubber for several metal elements (Ag, As, B, Ba, Co, Cr, Hg, Mn, Ni, Pb, Sn, Sr, Ti, and V) and anions (F − , PO 4 3− , and AsO 4 3− ) in wastewater. 11–14 Studies have demonstrated that the performance of HCDs is closely related to their microstructures.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2020) compared the BMS cement prepared by MgO derived from the calcination of brine precipitation products and LBM, and the former showed a higher early strength. Chen et al (2018) investigated the BMS cement prepared using light burnt dolomite and found that the BMS cement prepared using magnesia at a calcination temperature of 850°C had the highest strength. In our previous report (Wu et al 2018), the magnesium-rich by products obtained in the production of lithium carbonate from salt lake were used to prepare BMS cement.…”
Section: Introductionmentioning
confidence: 99%